Bão mặt trời tháng 9-2005 và phản ứng của điện ly quan trắc tại Tp Hồ Chí Minh - Hà, Trần Quốc (Vietnam Journal of Earth Sciences, 2009)
The solar storms in September 2005 and response of the ionosphere observed in Ho Chi Minh City